The combination of turnaround management, blue ocean strategies and disruptive innovation as tools in guiding companies in overcoming their recession problems and develop a long- term healthy economic performance - Andreas, Karaoulanis (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
The contemporary financial environment creates several uncertainty obstacles for a variety of companies all over the globe. In order to be able to escape from such distress situations, companies need to develop a certain set of strategies which they should implement in the right way. Blue oceans strategy, turnaround management, disruptive innovation and strategy as simple rules are some of the core strategic approaches the author suggests in order companies to overcome crisis and sustain a long- term healthy economic performance.